Influence of spray mixture volume and flight height on herbicide deposition in aerial applications on pastures - Oliveira, M.a.p. (2014)
The objective of the present study was to analyze the influence of spray mixture volume and flight height on herbicide deposition in aerial applications on pastures. The experimental plots were arranged in a pasture area in the district of Porto Esperidião (Mato Grosso, Brazil). In all of the treatments, the applications contained the herbicides aminopyralid and fluroxypyr (Dominum) at the dose of 2.5 L c.p. ha-1, including the adjuvant mineral oil (Joint Oil) at the dose of 1.0 L and a tracer to determine the deposition by high-performance liquid chromatography (HPLC) (rhodamine at a concentration of 0.6%). The experiment consisted of nine treatments that comprised the combinations of three spray volumes (20, 30 and 50 L ha-1) and three flight heights (10, 30 and 40 m). The results showed that, on average, there was a tendency for larger deposits for the smallest flight heights, with a significant difference between the heights of 10 and 40 m. There was no significant difference among the deposits obtained with the different spray mixture volumes.